Hypermedia-based Poetries by Poetess, Anne Ranasinghe on Development of Adjectives - MB Nowzath; S Umashankar; MR Rishad Muhammed; MJF Sujani (COMPETITIVE: Journal of Education, 2025)
Hypermedia-based Anne Ranasinghe’s poetry learning; refers to facilitate Anne Ranasinghe’s poetries including graphs, images, animation, sound and hypertext with constructive learning tactics exhibits a central part in the success of the students learning English as a second language. This study was steered to recognize the output of hypermedia-based teaching in the adjective development followed in the Certificate in Professional English (CPE) with factual learning styles: activities and arrangements in recitation with video and audio-based method. The term adjective refers to a word that modifies or describes a noun or pronoun and explains the qualities of someone or something independently or in comparison to something else. The study was conducted with participants of CPE course at the Sri Lanka Youth Vocational Training Centre of National Youth Services Council. Ninety students from CPE – class - A were engaged as an experimental group and equal numbers of students from class - B were engaged as the controlled group. A pre-test was led for both the groups to find out the previous proficiency level of adjectives of the students and the mean differences were found to be negligible for both the groups from the pre-test. Later, the experimental group used hypermedia-based learning based on selected learning strategies for six months with ninety hours learning while the controlled group was taught without the use of hypermedia-based Anne Ranasinghe’s poetry learning. After six months a post-test was conducted for both the groups. When the post-test was conducted the mean (-0.091) was slightly improved for the group - B than the pre-test, and the mean (-2.971) was significantly improved for the group - A in the post-test. Thus, it is found that there is a positive relationship between the hyper-media based learning and the performance in adjective development. The research findings indicate that hyper-media based Anne Ranasinghe’s poetry learning improves adjective development of the learners of English as a second language.